Unique pharmacology of a novel allosteric agonist/sensitizer insulin receptor monoclonal antibody - Simon A. Hinke; Anne M. Cieniewicz; Thomas Kirchner; Katharine D'Aquino; Rupesh Nanjunda; Jason Aligo; Robert Perkinson; Philip Cooper; Ken Boayke; Mark L. Chiu; Steve Jarantow; Eilyn R. Lacy; et al. (Elsevier, 2018)
Objective: Insulin resistance is a key feature of Type 2 Diabetes (T2D), and improving insulin sensitivity is important for disease management. Allosteric modulation of the insulin receptor (IR) with monoclonal antibodies (mAbs) can enhance insulin sensitivity and restore glycemic control in animal models of T2D. Methods: A novel human mAb, IRAB-A, was identified by phage screening using competition binding and surface plasmon resonance assays with the IR extracellular domain. Cell based assays demonstrated agonist and sensitizer effects of IRAB-A on IR and Akt phosphorylation, as well as glucose uptake. Lean and diet-induced obese mice were used to characterize single-dose in vivo pharmacological effects of IRAB-A; multiple-dose IRAB-A effects were tested in obese mice. Results: In vitro studies indicate that IRAB-A exhibits sensitizer and agonist properties distinct from insulin on the IR and is translated to downstream signaling and function; IRAB-A bound specifically and allosterically to the IR and stabilized insulin binding. A single dose of IRAB-A given to lean mice rapidly reduced fed blood glucose for approximately 2 weeks, with concomitant reduced insulin levels suggesting improved insulin sensitivity. Phosphorylated IR (pIR) from skeletal muscle and liver were increased by IRAB-A; however, phosphorylated Akt (pAkt) levels were only elevated in skeletal muscle and not liver vs. control; immunochemistry analysis (IHC) confirmed the long-lived persistence of IRAB-A in skeletal muscle and liver. Studies in diet-induced obese (DIO) mice with IRAB-A reduced fed blood glucose and insulinemia yet impaired glucose tolerance and led to protracted insulinemia during a meal challenge. Conclusion: Collectively, the data suggest IRAB-A acts allosterically on the insulin receptor acting non-competitively with insulin to both activate the receptor and enhance insulin signaling. While IRAB-A produced a decrease in blood glucose in lean mice, the data in DIO mice indicated an exacerbation of insulin resistance; these data were unexpected and suggested the interplay of complex unknown pharmacology. Taken together, this work suggests that IRAB-A may be an important tool to explore insulin receptor signaling and pharmacology. Keywords: Insulin, Insulin receptor, Positive allosteric modulator, Monoclonal antibody, Diabetes